Kadar Estradiol dan Progesteron Serum, Tampilan Vulva dan Sitologi Apus Vagina Kambing Bligon Selama Siklus Birahi - Widiyono, Irkham; Putro, Prabowo Purwono; -, Sarmin; Astuti, Pudji; Airin, Claude Mona (Jurnal Veteriner; Vol 12 No 4 (2011), 2012)
A study was carried out to determine the serum estradiol and progesterone concentration, vulvaappearance, and vaginal cytology during estrous cycle in bligon goat. Four female non pregnant bligongoats (Indonesian indigenous) were used in this research. They were clinically healthy and showed normalestrous cycle. Estrous state was examined by using biological method. When the animals showed acceptanceto be mounted by a buck, they were confirmed as the first day of estrous cycle (estrous phase). Collectionof blood sample, preparation of vaginal smears, and measurement of some physical genital parameterswere conducted by standard veterinary clinical methods at day 11, day between 3-5, day between 6-16, andday between 17-19 of estrous cycle. Enzyme linked immunosorbent assay (ELISA) was used to determineserum progesterone and estradiol concentrations. Mean difference of each parameter was analyzed byanalyses of variance (Anova), followed by Tuckey HSD. The serum estradiol concentration ranged between211.25-247.77 pg/ml. Peak of the estradiol was occurred at the first day of estrous phase, namely 247.77pg/ml and to decrease at day 3-16. The serum progesterone concentration was at the level of 0.21-0.70 ng/ml and showed a significant increase at day 6-16 (p<0.05). The specific physical genital changes (swellingvulva, reddish mucous membrane of vulva, and excretion of viscous transparent vaginal discharge) wereidentified as the animals were at the estrous phase. Composition of exfoliative vaginal cytology did notshow any specific and consistent changes throughout the estrous cycle. Superficial and intermediate cellswere very dominant (>60%) during estrous cycle. In conclusion, serum estradiol, progesterone, the vulvaappearance combined with sexual receptivity could be a good estrous predictor for female cycling bligongoat.
Keywords: bligon goat, estradiol, progesterone, vaginal cytology vulva